National Survey of Pharmacy Practice at MOH Hospitals in Saudi Arabia 2016-2017: Pharmacy Management and Resource - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia 2016- 2017: Pharmacy Management and resources. Methods: It is a 4-months cross-sectional National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia. The study consisted of two parts; the demographic information and the second part contained eighty-five questions divided into nine domains drove from American Society of Health-System Pharmacists (ASHP) and Saudi Pharmaceutical Society (SPS) survey, the international standard of Joint Commission of Hospital Accreditation, and the local standards of Saudi Center of healthcare accreditation. An electronic questionnaire was distributed to one hundred eighty-five directors of pharmacies at MOH hospitals. The study discussed and analyzed National Survey of Pharmacy Practice at MOH hospitals in Saudi Arabia: Pharmacy Management and resources. All analysis was done through survey monkey system. Results: The survey questionnaire was distributed to 185 hospitals, the rate of reply, was 105 (56.75%). The most of the hospital pharmacies provide their services to the adult emergency (91.18%), medical (90.82%), and surgical patients (87.76%). The highest number of prescriptions annually was adults emergency (5,094,000), Pediatrics emergency (3,357,000) and medical services (2,340,000). The majority of pharmacy services consisted of outpatient pharmacy 88 (92.63%), inpatient pharmacy 81(82.65 %%), pharmacy store 77 (77.00%), and emergency pharmacy 63(68.48%). The seldom finding of pharmacy services were satellite pharmacy 7(8.33%), clinical pharmacy 7 (10.47%), followed by repackaging system 27 (31.76%) and Intravenous admixture servicers 29(32.22%). The total number prescriptions dispensed were (32,643,000) annually with (25,110.01) prescriptions per hospital per year. The total numbers of pharmacists were (953), and pharmacy technicians were (1251). The average space size of hospital pharmacy was (113.98 m2 ) with the highest space, outpatient pharmacy (32.16 m2 ) followed by inpatient pharmacy (24 m2 ) and pharmacy store (22.42 m2 ). Conclusion: Most of the hospital pharmacies missed some essential of pharmacy practice with emphasis on Human Resources and clinical pharmacy services. Implementing MOH pharmacy strategic plan with close monitoring is required for all hospitals in Saudi Arabia.
Keywords: Pharmacy management; Human resources; Ministry of Health; Saudi Arabia